HAPS MOVEMENT ANALISYS AS PREMINARY STUDY AT APPLICATION OF OPTIC COMMUNICATION INTER HAPS - Ary Murti, Muhammad
High Altitude Platform System (HAPS) is a system that has almost the same principle with that of satellite but at an altitude about 20-50 km. This altitude makes the coverage area small but is better in cost, maintenance and development or upgrading. because the aircraft of HAPS is more convenient for launching and landing. HAPS can use airplane or zeppelin to bring payload such as telecommunication equipment. Communication between two HAPS can use optical (Laser) communication through free space [8,9]. so it makes the transfer rate up to in order of Giga Bps [4,5,9] and lower power consumption than that of radio communication. In laser communication through free space. to transfer the data. it need Line of Sight (LOS) between transmitter and receiver [5]. At altitude 20-50 km. atmosphere has properties of temperature lower than -77°C (-5°C/km), humidity 4% and speed of wind up to 40 m/s [7] The RAPS movement can break the LOS. To keep LOS, it needs a good Pointing, Acquisition, and Tracking (PAT) system. Pointing is the process to direct the laser beam to a target point. Acquisition is the process to determine transmitter position by calculating the angle of laser beam source. Tracking is the processes that includes Pointing and Acquisition process to maintain the LOS condition [5]. This thesis analyzes the movement of HAPS that correlates with application in optical communication between HAPS. Analyses is made to determine the maximum velocity of HAPS movement. The discussion starts with mathematical model of motor and its feedback system (acquisition process) that are used for tracking system and design PID controller to produce better performances. Moreover, it finds out the geometry of laser beam that can be produced by optical antenna. By using data of laser beam geometry and performance of' tracking system. definition of maximum velocities are determined, for both rotation and translation movement. Outcome of this research are the performance of tracking system that is already satisfied by PID controller, and optical antenna can make laser beam with 0.0825° of angle for 200 km distance between transmitter and receiver. Rotation movement has more effect than translation movement at tracking system to maintain LOS. If position and attitude control of HAPS aircraft can keep velocity under 90/sec. then optic communication between two HAPS can be implemented use that tracking control.